Management styles explained - Boland, Michael; Rutigliano, Katrina; Wilson, Joe; Video Education Australasia (United Kingdom : Video Education Australasia, 2011)
Management styles are characteristic ways of making decisions and relating to subordinates. The predominant management styles are commonly defined as autocratic, persuasive, consultative, participative and laissez faire. While leaders often exhibit a preference for a particular style of management, it is argued the different styles of leadership should be employed dependent upon the culture of the business, the nature of the task, and the nature of the workforce. Effective management will ensure that the objectives of an organisation are met. This informative program examines the five management styles, their characteristics, advantages and disadvantages and application to various management situations.
Voice over: Jane Nolan.
DVD format
Keywords: Management; Industrial management; Executives -- Attitidues